Peptide microarray-based characterization of antibody responses to host proteins after bacille Calmette–Guérin vaccination. (March 2017) - Valentini, Davide; Rao, Martin; Rane, Lalit; Rahman, Sayma; Axelsson-Robertson, Rebecca; Heuchel, Rainer; Löhr, Matthias; Hoft, Daniel; Brighenti, Susanna; Zumla, Alimuddin; Maeurer, Markus
Summary: Background: Bacille Calmette–Guérin (BCG) is the world's most widely distributed vaccine, used against tuberculosis (TB), in cancer immunotherapy, and in autoimmune diseases due to its immunomodulatory properties. To date, the effect of BCG vaccination on antibody responses to host proteins has not been reported. High-content peptide microarrays (HCPM) offer a unique opportunity to gauge specific humoral immune responses. Methods: The sera of BCG-vaccinated healthy adults were tested on a human HCPM platform (4953 randomly selected epitopes of human proteins) to detect specific immunoglobulin gamma (IgG) responses. Samples were obtained at 56, 112, and 252 days after vaccination. Immunohistology was performed on lymph node tissue from patients with TB lymphadenitis. Results were analysed with a combination of existing and novel statistical methods. Results: IgG recognition of host peptides exhibited a peak at day 56 post BCG vaccination in all study subjects tested, which diminished over time. Primarily, IgG responses exhibited increased reactivity to ion transporters (sodium, calcium channels), cytokine receptors (interleukin 2 receptor β (IL2Rβ), fibroblast growth factor receptor 1 (FGFR1)), other cell surface receptors (inositol, somatostatin, angiopoeitin), ribonucleoprotein, and enzymes (tyrosine kinases, phospholipase) on day 56. There was decreased IgG reactivity to transforming growth factor-beta type 1 receptor (TGFβR1) and, in agreement with the peptide microarray findings, immunohistochemical analysis of TB-infected lymph node samples revealed an overexpression of TGFβR in granulomatous lesions. Moreover, the vesicular monoamine transporter (VMAT2) showed increased reactivity on days 112 and 252, but not on day 56 post-vaccination. IgG to interleukin 4 receptor (IL4R) showed increased reactivity at 112 days post-vaccination, while IgG to IL2Rβ and FGFR1 showed decreased reactivity on days 112 and 252 as compared to day 56 post BCG vaccination. Conclusions: BCG vaccination modifies the host's immune landscape after 56 days, but this imprint changes over time. This may influence the establishment of immunological memory in BCG-vaccinated individuals.